Tumor suppressing function of SLC16A7 in bladder cancer and its pan-cancer analysis - Mingjie Xu; Jiatong Zhou; Jiancheng Lv; Yu Zhang (BMC Cancer)
Abstract Background Bladder cancer (BCa), a prevalent malignancy of the urinary tract, is associated with high recurrence and mortality rates. SLC16A7, a member of the solute carrier family 16 (SLC16), encodes monocarboxylate transporters that are involved in the proton-coupled transport of metabolites, including lactate, pyruvate, and ketone bodies, across cell membranes. Evidence suggests that SLC16A7 exhibits variable expression in cancers and may influence tumor development, progression, and immune regulation. This study examined the role of SLC16A7 in cancer prognosis, progression, and immune regulation, focusing on BCa. Methods A comprehensive analysis was conducted to evaluate the clinical and immunological relevance of SLC16A7 across multiple cancer types using data from 33 tumor datasets from ‘The Cancer Genome Atlas (TCGA). ’ Associations between SLC16A7 expression and clinicopathological features, prognostic indicators, tumor mutation burden (TMB), microsatellite instability (MSI), immune cell infiltration, and immune-related gene expression were systematically analyzed. Experimental validation was performed to assess SLC16A7 expression in the BCa tissues and cell lines. The prognostic value of SLC16A7 was confirmed using clinical follow-up data from an independent patient cohort. Functional studies included proliferation assays to investigate the effect of SLC16A7. CD8 + T cells were obtained from the peripheral blood of healthy donors and stimulated using CD3 and CD28 antibodies in combination with recombinant IL-2. To investigate the immunological role of SLC16A7, co-culture experiments were performed between BCa cells and activated CD8 + T cells. Additionally, CD8 + T cell chemotaxis assays and ELISA analyses were conducted to evaluate the immune responses mediated by SLC16A7. Results SLC16A7 expression was downregulated in 16 cancer types, including BCa, and upregulated in three cancer types. Its expression was significantly associated with tumor stage in four cancers and showed both positive and negative correlations with prognosis, depending on the cancer type. Genomic analyses revealed significant associations between SLC16A7 and TMB in 13 cancer types and MSI in 11 cancer types. Pathway enrichment analyses (Hallmark-GSEA and KEGG-GSEA) indicated strong associations between SLC16A7, immune responses, and tumor progression. Immune infiltration analysis showed a predominantly positive association between SLC16A7 expression and immune cell infiltration, except in low-grade gliomas (LGG). CIBERSORT analysis demonstrated that SLC16A7 expression correlated positively with resting memory CD4 T cells, eosinophils, monocytes, resting mast cells, and memory B cells and negatively with activated memory CD4 T cells, M1 macrophages, follicular helper T cells, M0 macrophages, and CD8 T cells. SLC16A7 expression was also significantly associated with the expression of immune-regulatory molecules. Experimental validation showed reduced SLC16A7 expression in BCa tissues and cell lines compared to that in their normal counterparts. Kaplan-Meier survival analysis indicated that higher SLC16A7 expression was correlated with better overall survival in patients with BCa. Functional assays revealed that SLC16A7 inhibited BCa cell progression and promoted the chemotaxis and tumor-killing ability of CD8 + T cells in the BCa tumor microenvironment (TME). Conclusions SLC16A7 exhibits tumor-suppressive properties, with downregulation in most cancers, and is associated with favorable prognosis and enhanced immune responses. SLC16A7 functions as a tumor suppressor in BCa and is associated with improved survival outcomes. These findings suggest that SLC16A7 is a potential biomarker for cancer diagnosis and prognosis.